Analytical Study of Javelin Landing Angle and Horizontal Distance (Achievement) of Iraqi Javelin Thrower Champion - Saab, Mohammed; Thamer, Ahmed (Journal of Physical Education, 2019)
The research aim at identifying some biomechanical variables of javelin throwing and landing as well as identifying the relation between javelin landing angle and the horizontal distance achieved by the Iraqi javelin champion. The researchers used the descriptive method. The subject was Kerar Raad, the champion of Athletics in Iraq 2017 who achieved (70.76m). The researchers shot six javelin throws of Kerar in Iraqi clubs’ championship held by the Iraqi federation for athletics in ministry of youth and sport track and field on Friday 8/3/2019.  The researchers concluded a relation between javelin landing angel and the horizontal distance achieved by the Iraqi championship that is when the angle of landing decreases the achieved distance increases.